Students' Perception Towards Artificial Intelligence in Higher Education in India (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This research examines students' perceptions of Artificial Intelligence (AI) in higher education in India. Data was collected from 100 students from different fields from engineering, management and science and used a quantitative research study design. A structured questionnaire used with a five-point Likert scale evaluated categories including Awareness, Perception, Perceived Benefits, Implementation, Adoption, and Challenges. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to explore the data. The result of the measurement model confirmed construct reliability and validity. The structural model's findings showed that high awareness of students predicts perception ,perception strongly predicts implementation, and implementation significantly predicts adoption. Perception and challenges , on the other hand, had no visible impact on adoption, suggesting that barriers are less powerful than anticipated. The results shown that the main factors influencing the adoption of AI in higher education are effective implementation and the way the implementation introduced . By highlighting implementation as a crucial mediator in adoption models, the work adds theoretical value and has applications for educators and policymakers.